Halal Analysis of An Aquatic Animal(pangasius sutchii) using RT-PCR For Detection of Porcine DNA - Tengku Nor Hidayati, Tengku Zainal Abidin; Hasan, Ahmad (Universiti Malaysia Pahang, 2016)
Pig (Sus sp.) and pig by products are considered as najasa (impurities) in Islam and forbidden in muslim consumer product. Animal fed on najasa are categorised as al-jāllalah (contaminated animals) which are allowed to be consumed as long as they have been quarantined for a certain period of time. During this quarantine period the animals will have undergone a natural purification process or istibra’. Patinfish (pangasiussutchi) are commonly consumed in Malaysia and maybe fed on najasa. This study was conducted to investigate the detection of pig DNA for patin fish(pangasiussutchii) after feeding with pig offal, based on the absence of the DNA in tank water, gut, skin and fish fillet by real time polymerase chain reaction (RT-PCR). A total of 3 fish samples (n=3*3) with three replicates for each samples were obtained from river located in Temerloh Pahang and fed with pig offal. Fish gut and the positive control was positive towards porcine DNA, however tank water, skin and fish fillet was negative towards porcine DNA.